Isolation and characterization of a gene encoding farnesyl diphosphate synthase from Panax vietnamensis Ha et Grushv - Giang, Nguyen Van; Ly, Luu Han; Hang, Pham Le Bich; Hien, Le Thi Thu (Academia Journal of Biology, 2021)
Panax vietnamensis Ha et Grushv. is a species of the genus Panax native to Central Vietnam, containing a family of triterpene saponins named ginsenosides. This group of biomolecules possesses valuable therapeutic properties against cancer, hepatitis, diabetes, inflammation as well as stress and anxiety. Farnesyl diphosphate synthase (FPS) is a key enzyme participating in the ginsenoside biosynthesis pathway. In this study, a FPS gene from P. vietnamensis (PvFPS) was isolated and characterized. The PvFPS cDNA contained an open reading frame of 1032 bp, encoding a polypeptide chain of 342 amino acid residues. Nucleotide sequence comparison showed that FPS was highly conserved among most species, with two Aspartate-rich motifs responsible for product chain length determination strongly sustained. PvFPS was closely related to those of the same genera and order and differed from those from other kingdoms. PvFPS expression was detected at a greater level in root tissues than in leaves in all ages. Our findings provided information concerning the properties of a crucial gene in the ginsenoside biosynthesis, thus enhancing our understanding of this important pathway.